THE INFLUENCE OF SERVICE QUALITY AND ONLINE TICKET PURCHASE SYSTEM ON CUSTOMER SATISFACTION OF TRAIN SERVICE USERS: (A Study at PT. K.A Sribilah for the Medan-Rantauprapat Route) - Sari, Mega Novita; Dirbawanto, Nana Dyki (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The low level of customer satisfaction at PT K.A generally arises because the quality of service provided is not in accordance with the expectations of railway customers. Low customer satisfaction will result in customers being reluctant to use rail transportation services. This study aims to analyze the influence of service quality and the online ticket purchasing system on customer satisfaction with Sribillah train services. The influence of the related variables, namely the quality of service and online ticket purchases, will be analyzed both partially and simultaneously on customer satisfaction. This study employs a quantitative research approach with an associative methodology. Sampling was done using purposive sampling techniques, involving 100 respondents as the research sample. Primary data for this study were obtained through the distribution of conventional questionnaires, and secondary data was gathered through a literature review. The analytical methods used include validity tests, classical assumption tests, reliability tests, multiple linear regression analysis, and hypothesis testing. The results of the research indicate that the service quality variable (X₁) and the online ticket purchasing system variable (X₂) both have a significant effect on customer satisfaction when considered separately. Furthermore, when these variables are considered together, they also have a significant impact on customer satisfaction. Based on the coefficient of determination test, there is a fairly strong relationship between service quality and online ticket purchases in influencing customer satisfaction, with an R value of 0.837. Through the adjusted R square, it is determined that service quality and online ticket purchases contribute to customer satisfaction by 31%.